Pengaruh Faktor Pendidikan Remaja dan Ekonomi Keluarga Dengan Sikap Untuk Memutuskan Menikah di Usia Muda di Desa Prapag Kidul Losari Brebes - Maemunah, Maemunah; Muhlisin, Abi (Jurnal Kesehatan, 2013)
Young age marriage may give negative impact if it is happened without age and phsycosocialmaturity. The negative impacts that may be occured were the increase of divorce cases, broken school,the risk of mother mortality rate, risk of cancer cervic, and also the risk of infant mortality rate. Thisresearch was descriptive correlational with retrospective approach. The number of respondents were 50people in Prapag Kidul, Losari, Brebes. Data of economic and educational level and attitude to decidemarriage in young age were obtained using questionarre. The Pearson Product Moment was used todetermine the correlation between those variables. Result of this research showed that young agemarriage was majority happened in teenagers with low level of education, low level of parent?s education,and low level of economic status.